Narracja skandalu obyczajowego. Sprawa Durczoka czy afera „Wprost”? - Mazur, Rafał (Słowo. Studia językoznawcze, 2016)
The aim of the article is description of media scandal narratives on the example of scandal with editor of “Fakty” Kamil Durczok, who was accused by “Wprost” of mobbing and harassment of journalists. The research material includes articles published in the “Wprost” and “Newsweek” magazines, newspapers: “Fakt” and “Super Express” and posted on the websites: wpolityce.pl and se.pl. The article indicates differences in meaning between lexemes that are used to present a specific vision of events, such as: sprawa, afera, skandal and derivative nouns with suffix -gate. The article presents narrative structures that are characteristic for the scandal. Those structures include character creation, his activities and intentions, and obstacles encountered during the attempt of achieving his goal. Analysis of the material made it possible to distinguish two opposing rhetorical strategies: aggressive and defensive. Those strategies can be used to successively attack and defend of those involved in the scandal. The article also presents how these strategies can be used to create opposing visions of reality.